Examining the Social Function of Dramatic Rituals of Mazandaran with Emphasis on Three Rituals of tir mā sizeŝu, bisto šeše aydimā, and čake se mā - Ahmadzadeh, Fatemeh; Mohandespour, Farhad (Journal of History Culture and Art Research, 2017)
This study investigates the social functions of Mazandaran ancient rituals and examines the relationship between dramatic rituals and indigenous cultures from the past, and the effect of traditions left by the ancestors in today’s society. Geographical domain of this study is entire Mazandaran from East to West, and it is tried to consider the quality of performing the rituals and sanctity of these rituals. This study includes an overview of research, literature and research history, theories of social function of dramatic rituals of Mazandaran, data analysis, and discussion and conclusion. Library and field methods are used to collect the required data on a large scale. In conclusion, it could be argued that further understanding of common beliefs among the people of Mazandaran now and in the past could prevent the disintegration of generations, and it should be noted that all past beliefs and rituals of Mazandaran do not have suitable capabilities to be implemented in today’s semi-modern generation and are just for reminding and genreal knowledge.